The influence of Senior High School Student Factors and Teacher-Student Interaction on Student Performance in Mathematics in the Cape Coast Metropolis - Awoniyi, F.; Ampadu, E. (My University, 2018)
A total of 3,342 eleventh graders of 69 intact classes were randomly chosen along with their 57 teachers from ten public Senior High Schools in the Cape Coast Metropolis. The research employed a sequential explanatory mixed methods design. Four research instruments namely questionnaires, observation schedule, interview guides and achievement test were used to collect the data. The data collected from quantitative sources were analysed using inferential statistics and frequency counts. While those collected from interviews were analysed qualitatively and presented as narrative with some examples. Findings revealed that the variables: student anxiety, student attitude, student motivation and teacher-student relationship jointly explained 19% of the variance in achievement scores and attitude emerged as salient predictors of student achievement in mathematics and the sub constructs of the four variables collectively explained 44% of the variance in achievement scores. The implications of the results for the teaching and learning of mathematics are discussed.
Seminar
Keywords: Mathematics; Senior High School; Motivation; Anxiety; Attitude; Teacher-student relationship; Performance